Sprawa odwołania wojewody lwowskiego Kazimierza Grabowskiego - Koredczuk, Józef (Lʹvìvsʹkij nacìonalʹnij unìversitet ìmenì Ìvana Franka, 2021)
Kazimierz Grabowski was the first voivode of Lviv after Poland had regained independence and after the eastern border of the Republic of Poland had been demarcated and after the administrative division in the eastern borderlands had been introduced. He becamea publicly known figure, being one of the participants in the attack on the Chief of State, Józef Piłsudski, in September 1921. In 1923, when as a part of the so-called the government of “Chjeno-Piast” Władysław Kiernik became the Minister of the Interior, Grabowski fell into a conflict with him, as a result of which Grabowski was dismissed from the position of voivode. Grabowski’s appeal against this decision was the subject of proceedings before the Supreme Administrative Tribunal. This court proceeding sshowed that the Minister’s decision was inconsistent with the provisions on the appointment of voivodes and that the Minister exceeded his powers in this respect, combined with the violation of the powers of the Council of Ministers and the Head of State (President of the Republic of Poland). It was also inconsistent with the basic legal acts defining the status of the voivode at that time, i.e., the Act of August 2, 1919 on the organization of administrative authorities of the II instance (called the act on the organization of provinces) and inconsistent with the Act of February 17, 1922 on the state civil service (the so-called official pragmatics). The described case is an example of some politicians’ approach to obeying the law, which we also encounter today.
Keywords: Grabowski, Kazimierz (1866-1932); minister spraw wewnętrznych; Najwyższy Trybunał Administracyjny; państwowa służba cywilna; Kiernik, Władysław (1879-1971); wojewoda lwowski; Mìnìstr vnutrìšnìh sprav; Viŝij admìnìstrativnij tribunal; deržavna služba; lʹvìvsʹkij voêvoda